Red Bay Psyllid, Trioza magnoliae (Ashmead) (Insecta: Hemiptera: Sternorrhyncha: Psyllidae) - Donald W. Hall (EDIS, 2009)
EENY-438, a 5-page illustrated fact sheet by Donald W. Hall, is part of the Featured Creatures collection. It describes this psyllid which causes galls on the leaves of native species of Persea bay trees — its distribution, description, life cycle and biology, and economic importance. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009.